2011
DOI: 10.4314/ajpsy.v14i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorders (ASD) in Africa: a perspective

Abstract: Background: The universal occurrence of autism spectrum disorders (ASD) was queried about twenty-six years ago. It was thought to occur only in western industrialized countries with high technological development. Over the last decade, knowledge about ASD and its prevalence has been documented as being on the rise in different regions of the world, with most literature coming from the western world -the situation in Africa on aspects of ASD remain unclear. Methods: Literature cited in Pubmed over the last deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 15 publications
4
106
1
Order By: Relevance
“…A recent global survey did not support geographical variation in prevalence, but acknowledged limited prevalence studies from lower-middleincome countries (Elsabbagh, Divan, Koh, Kim, Kauchali, Marc í n, et al, 2012). There have been limited epidemiological studies of ASD in lowermiddle-income countries, although there have been individual country papers (Bakare & Munir, 2011;Daley, 2002). This paper reviews the status of early identifi cation and intervention in LMIC.…”
Section: Introductionmentioning
confidence: 98%
“…A recent global survey did not support geographical variation in prevalence, but acknowledged limited prevalence studies from lower-middleincome countries (Elsabbagh, Divan, Koh, Kim, Kauchali, Marc í n, et al, 2012). There have been limited epidemiological studies of ASD in lowermiddle-income countries, although there have been individual country papers (Bakare & Munir, 2011;Daley, 2002). This paper reviews the status of early identifi cation and intervention in LMIC.…”
Section: Introductionmentioning
confidence: 98%
“…However, in other areas where less research has been undertaken, information regarding ASD can be partial and fragmented. Significant challenges are faced regarding assessment, identification and appropriate treatment across Sub-Saharan Africa in general (Bakare and Munir, 2011a;Ruparelia et al, 2016) and within Nigeria in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Studies done in several countries have revealed inadequacies in knowledge about autism among doctors, with a variation between primary care providers and specialists [4][5][6] . The average delay from first presentation to diagnosis is estimated to be 4 years 2 .…”
Section: Introductionmentioning
confidence: 99%